Analisis keterampilan metakognitif siswa dalam pemecahan masalah matematika aplikasi perbandingan(pada siswa kelas vii mts n surakarta 2 tahun ajaran 2015/2016) - Apriyanti, Ririn, Masduki, S.Si, M.Si (2016)
This research was conducted with the aim of describing the metacognitive skills of students in solving application problems comparisons odd semester of seventh grade students of MTs N Surakarta 2. The research is a qualitative descriptive. The study was conducted on students of class VII MTs N Surakarta 2 second semester of 2015/2016 academic year by taking three students as research subjects. Data collection techniques of observation, interviews, and documentation. The validity of the data using a triangulation method. Data analysis techniques with data reduction, data presentation, and conclusion. Metacognitive skills of students aspects of prediction, showing that (1) some students have not been able to understand the issues in the matter appropriately, (2) some students an understanding on what is known in the matter, and (3) some students have not been able to understand and determine which is asked in the problem in comparison application. Facts on the ground which refers to aspects of planning metacognitive skills indicate that students tend to be able to transform into a mathematical model about the story and the students were able to determine the exact settlement strategy in solving application problems comparisons. Metacognitive skills of students monitoring aspects of the facts on the ground by a few students have not been able to recall and determine the formula used appropriately and students tend to not be able to apply the concepts used appropriately in resolving problems comparison application. Metacognitive skills evaluation aspects as complement the predictive aspect aspect, planning and monitoring. Facts on the ground that the researchers obtained results metacognitive skills aspects of the evaluation on the accuracy of the students in the process of calculation has not been done by some students and students tend to not do the re- examination after work, so it is not aware of the answer wrong